Connectivity of vegetation diversity, carbon stock, and peat depth in peatland ecosystems - R. Garsetiasih; N.M. Heriyanto; W.C. Adinugroho; H. Gunawan; I W.S. Dharmawan; R. Sawitri; I. Yeny; N. Mindawati; . Denny (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Peat swamp forest ecosystems are fragile ecosystems with different peat depths according to the level of peat formation. Moreover, a peat swamp forest can have diverse vegetation and high carbon stocks. Thus, caution should be taken in the sustainable management of a peat swamp forest. However, the connection between vegetation diversity, carbon stocks, and peat depths has not been widely studied in efforts to conserve vegetation and peatlands. This study aimed to analyze the connection between vegetation diversity, carbon stocks, and peat depths in the Kahayan Sebangau Peat Hydrology Unit.METHODS: Plots at the peat depths of four sites were studied: site 1 (<50 cm), site 2 (393-478 cm), site 3 (479-564 cm), and site 4 (565-649 cm).CONCLUSION: All Pearson correlation values between peat depth, vegetation diversity, and carbon stock were positive with each other. This shows that peat depth, vegetation diversity, and carbon stock are interdependent and connected to one another.